2020
DOI: 10.1108/apjml-09-2019-0554
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of perceived social support in discount stores in Korea

Abstract: PurposeThe purpose of this study is to bridge the gap in literature to examine social support that customers receive from their relationships with frontline service providers in discount stores.Design/methodology/approachIn total, 381 consumers are accessed through an online survey administered by an online research company in South Korea. The authors use the structural equation model (SEM) technique to test the proposed hypotheses.FindingsSocial support (emotional, instrumental, informational and appraisal) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Expressly, in the overall model, the maximum variance by single factor was 29.045. 1 www.wjx.cn Furthermore, the common latent factor (CLF) measured as suggested by Song et al (2019). The standard regression scores of a model with and without CLF were compared.…”
Section: Variation Of Responsesmentioning
confidence: 99%
“…Expressly, in the overall model, the maximum variance by single factor was 29.045. 1 www.wjx.cn Furthermore, the common latent factor (CLF) measured as suggested by Song et al (2019). The standard regression scores of a model with and without CLF were compared.…”
Section: Variation Of Responsesmentioning
confidence: 99%
“…According to them, service quality to the customers is more important than discount (Song et al, 2020;Al-dweeri et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [50] found that community emotional support is important. Community support increases current and potential donors' intentions [48], whereas social support helps individuals feel better and stay optimistic.…”
Section: Discussionmentioning
confidence: 99%
“…Caring, trust, encouragement, recognition, and a feeling of community are all forms of emotional support [41]. They also influence decision-making behaviour [40], customer satisfaction [50], well-being [51], and social commerce intention [52,53]. As proposed by [53], emotional support affects trust.…”
Section: H2 Informational Support Is Positively Related To Donation I...mentioning
confidence: 99%